Mapas Memes: Discursos Espaciais em Movimento - Zamur, Lucas Nigro (Universidade Federal de São Carlos, 2024)
This work focuses on artistic maps of the internet - meme maps, aiming to understand them as cybercultural forms of mapping, the result of a fusion of genres, which bends cartographic conventions in terms of satire, humor, and criticism. Bakhtinian theory is used to understand the dialectic between everyday ideologies and official ones, which are parodied in meme maps. Examples of meme maps are discussed from the perspective of critical and cultural cartography theories, while guiding the discussion. A contextual analysis of the discourses of the meme maps was carried out in relation to their extralinguistic dialogue, the movement and the incompleteness of their forms. We sought to understand the ideological tensions reproduced in the meme maps and their artistic character, which cannot be separated from the medium in which they circulate - the networks with their own dynamics. Finally, a reading of the artistic value of these works was proposed, considering the lightness of their movement as an alternative to the productive appropriation of humorous discourses.
Meme Maps: Spatial Discourses in Motion
Keywords: Mapas Memes; Cartografia Crítica; Cartografia Cultural; Cibercultura; Hiperarte; Meme Maps; Critical Cartography; Cultural Cartography; Cyberculture; Hyperart; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA